Asset Confiscation in Gold Pawn Corruption Cases : An Analysis from Islamic Law and Positive Law Perspectives - Aulia Fitriyatus Sholihah; Fadllan Fadllan; Erie Hariyanto; Rudy Haryanto (Universitas Al-Amien Prenduan Sumenep, 2025)
Corruption cases involving gold pawn (rahn) transactions within Islamic financial institutions highlight critical challenges related to sharia governance, fiduciary responsibility, and asset protection. Despite being founded on ethical and religious principles, sharia-compliant financial products remain vulnerable to financial crimes, particularly in high-value, asset-based transactions. This study examines asset confiscation mechanisms in a gold pawn corruption case in Pamekasan, Indonesia, analyzed through the perspectives of Islamic law and positive law. Employing a qualitative case study approach, this research utilizes statutory regulations, court-related legal documents, institutional reports, and secondary data from verified media and academic literature. The findings demonstrate that asset confiscation serves a dual function: as a legal instrument for state loss recovery under Indonesian anti-corruption law and as a normative mechanism aligned with Islamic legal principles such as amanah (trust), hifz al-mal (protection of property), justice, and public interest (maslahah). This study contributes to the literature by integrating Islamic jurisprudence with contemporary asset recovery discourse, emphasizing that asset confiscation is not merely a procedural legal act but a necessary governance mechanism to strengthen accountability and integrity within Islamic financial institutions. The research underscores the importance of harmonizing Islamic law and modern legal systems to restore public trust and enhance anti-corruption frameworks in sharia-compliant finance.